2012
DOI: 10.1155/2012/632838
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Potential of Acupuncture Points: Use of a Noncontact Scanning Kelvin Probe

Abstract: Objective. Acupuncture points are reportedly distinguishable by their electrical properties. However, confounders arising from skin-to-electrode contact used in traditional electrodermal methods have contributed to controversies over this claim. The Scanning Kelvin Probe is a state-of-the-art device that measures electrical potential without actually touching the skin and is thus capable of overcoming these confounding effects. In this study, we evaluated the electrical potential profiles of acupoints LI-4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…This has been demonstrated by Mussat and others. [56][57][58] Acupuncture needles with 1 metal (copper, silver, bronze, or an alloy) for the shaft and another metal for the handle, form tiny batteries. 9 Some acupuncture therapies use additional electrical stimulation (2-4 Hz) applied to the needles.…”
Section: Acupuncturementioning
confidence: 99%
“…This has been demonstrated by Mussat and others. [56][57][58] Acupuncture needles with 1 metal (copper, silver, bronze, or an alloy) for the shaft and another metal for the handle, form tiny batteries. 9 Some acupuncture therapies use additional electrical stimulation (2-4 Hz) applied to the needles.…”
Section: Acupuncturementioning
confidence: 99%
“…Indeed, the illustrations of the meridian system and acupoints may have made people misunderstand the essential meaning of the meridian system as actual substantial channels. Over the last few decades, many studies have suggested distinctive biophysical features of acupoints and the meridian system, such as high electrical conductance [1214], nitric oxide levels [9, 15], acupuncture sensation patterns [16], and possible relationships with connective tissue planes [17, 18]. Nevertheless, the scientific evidence on the biophysical existence of acupoints and meridians in humans still needs further explanation.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Due to the difficulty in defining or measuring Qi, few studies have been conducted on the mechanism of Qi or energy flow by acupuncture treatment, and all related studies have focused on the electrical properties such as the conductivity of acupuncture points 22 , 23 , 24 , 25 or measured biopotential changes only at some acupuncture points, not all meridians. 26 , 27 , 28 Thus, we aimed to observe the changes in electrical energy and to compare the electrical potential between the acupuncture and non-acupuncture points in twelve meridians.…”
Section: Introductionmentioning
confidence: 99%